Pengaruh Iklim Sekolah Terhadap Motivasi Belajar Siswa: Kajian Pustaka Kuantitatif - Esti Wati; Donna Boedi Maritasari; Atina Alawiyah; Rehanun (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study examines the effect of school climate on student learning motivation through a quantitative literature review approach. The quality of education is influenced by non-academic factors, one of which is school climate, which includes students' perceptions of teacher support, relationships between students, fairness, safety, and academic expectations, all of which can foster students' enthusiasm for learning and participation. Student motivation is a key driver of engagement and effectiveness in learning, and students with high motivation tend to have high achievement. The results of the two studies reviewed show a significant positive influence between school climate and student learning motivation. A conducive, supportive and positive school climate can foster intrinsic motivation and increase students' self-efficacy, while motivated students will contribute to a more dynamic and productive school atmosphere. Thus, creating a positive school environment is crucial to improving students' learning motivation and the overall quality of education.